2018
DOI: 10.1002/ecm.1300
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient remobilization in tree foliage as affected by soil nutrients and leaf life span

Abstract: Nutrient remobilization is a key process in nutrient conservation in plants and in nutrient cycling in ecosystems. To predict the productivity of terrestrial ecosystems, we thus need to improve our understanding of the factors that control remobilization. We studied the remobilization rates of several major nutrients (N, P, S, K, Ca, and Mg) in 102 forest ecosystems representing large environmental gradients at the country scale (France). Total amounts or availability of nutrients in soils were correlated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 108 publications
(189 reference statements)
1
37
2
Order By: Relevance
“…Hence, total soil P content need not represent an index of P availability for plants at the local scale, in contrast with previous studies reporting negative correlations between PRE and P total at the regional scale (Achat et al, 2018;Augusto et al, 2017). Inorganic phosphate represents the most biologically available form of soil P (Turner, 2008) while most of P total consists of stable organic or inorganic forms, for example sorbed to the surface of Al and Fe oxides or occluded in mineral compounds (Turner, 2008).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Hence, total soil P content need not represent an index of P availability for plants at the local scale, in contrast with previous studies reporting negative correlations between PRE and P total at the regional scale (Achat et al, 2018;Augusto et al, 2017). Inorganic phosphate represents the most biologically available form of soil P (Turner, 2008) while most of P total consists of stable organic or inorganic forms, for example sorbed to the surface of Al and Fe oxides or occluded in mineral compounds (Turner, 2008).…”
Section: Discussionmentioning
confidence: 80%
“…The strong negative correlations between nutrient resorption efficiencies (NRE and PRE) and nutrient concentrations in senescing leaves (N litter and P litter , respectively) mean that nutrient resorption efficiency mirrored nutrient resorption proficiency, that is the concentrations of nutrients in litterfall (Killingbeck, ). The poor correlations between nutrient resorption efficiency and nutrient concentration in green leaves suggest that foliar N or P concentrations are primarily determined by species‐specific features so that they cannot always be used as an indicator of nutrient status (Achat et al, ). Increasing δ 15 N (leaf‐soil) values across altitudinal gradients demonstrate that the plants utilized increasing fractions of organic N at higher altitudes especially through associated mycorrhizal partners (Amundson et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…showed that organic matter could be used to increase maize growth and Zn accumulations in the grain in a continuous manner. Achat et al . demonstrated that organic matter, specifically carbon, as well as the N ratio in regard to carbon and the P ratio in regard to K–Ca–Mg, is one of the factors influencing remobilization in plants.…”
Section: Discussionmentioning
confidence: 99%